Wychowanie w rodzinie jako czynnik kształtujący postawę tolerancji społecznej - Godawa, Grzegorz (Analecta Cracoviensia, 2013)
Tolerance is closely connected with upbringing. Forming one’s personality within the family environment influences the quality of attitudes in the society. The educational process aimed at developing tolerance emphasizes that the value of a person should always be most important. Partnership in the family which forms the basis for democratic upbringing is a crucial element helping to develop tolerance. The upbringing based on relationships which are not distorted may be very effective. To enable the family to base their life on genuine partnership it is necessary to refer to universal values during the educational process. Selfless love which should be the foundation of life and upbringing is the best guarantee of social tolerance.